2021
DOI: 10.14488/bjopm.2021.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of artificial intelligence on public employment and its impact on politics: A systematic literature review

Abstract: Goal: Public administration is constantly changing in response to new challenges, including the implementation of new technologies such as robotics and artificial intelligence (AI). This new dynamic has caught the attention of political leaders who are finding ways to restrain or regulate AI in public services, but also of scholars who are raising legitimate concerns about its impacts on public employment. In light of the above, the aim of this research is to analyze the influence of AI on public employment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…(3) peer-reviewed articles, which increases the quality of the results and the credibility of the research, (4) wider application of filters, and (5) immediate generation of search results in graphs and tables. Thus, based on the previous advantages, the use of a single scientific database has been accepted by the academic community [59]. By following the assumptions of Moher et al [56], this research uses the PRISMA Statement (also known as Preferred Reporting Item for Systematic Reviews and Meta-Analysis), which consists of a 27-item checklist and a four-phase flow diagram.…”
Section: Methodsmentioning
confidence: 99%
“…(3) peer-reviewed articles, which increases the quality of the results and the credibility of the research, (4) wider application of filters, and (5) immediate generation of search results in graphs and tables. Thus, based on the previous advantages, the use of a single scientific database has been accepted by the academic community [59]. By following the assumptions of Moher et al [56], this research uses the PRISMA Statement (also known as Preferred Reporting Item for Systematic Reviews and Meta-Analysis), which consists of a 27-item checklist and a four-phase flow diagram.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the well-known advantages of AI and robotics, current discussion often covers the risks of automation. Debates have focused more on the adaptability of jobs in DT than on replacing human labor [ 69 ]. Most studies suggest that complex socioemotional tasks continue to be performed by human beings, while cognitive-analytic tasks will be increasingly migrated to machines [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the several criticisms in the domain of AI concerning employment generation, the study by [ 37 ] has identified the lack of awareness between the AI utility and the tech-savvyness of labourers. Awareness of the public concerning the four intelligence processes such as mechanical, analytical, empathetic, and intuitive is highly essential in eliminating the negative stigma of AI hampering employment opportunities [ 38 ]. The researchers believe there exists a dormant need for public awareness which provides transparent knowledge on the pros of AI and eradicates ignorance and negative stigma.…”
Section: Literature Reviewmentioning
confidence: 99%